The instantaneous-space-phasor a powerful diagnosis tool - Milanez, D. L.; Emanuel, A. E. (Institute of Electrical and Electronics Engineers (IEEE), 2003)
This paper presents the instantaneous-space-phasor (ISP) definition and describes its properties and possible applications for three-phase systems. It is shown that the ISP provides the mathematical base for a new approach to the measurement of active, reactive, and apparent power. Moreover, the ISP helps separate the positive and negative-sequence components and fits perfectly into the Buchholz-Goodhue apparent power definition.
Keywords: power quality; powers definitions